Combination of the clustered regularly interspaced short palindromic repeats (CRISPR)‐associated 9 technique with the piggybac transposon system for mouse in utero electroporation to study cortical development. Issue 9 (18th June 2016) - Cheng, Man; Jin, Xubin; Mu, Lili; Wang, Fangyu; Li, Wei; Zhong, Xiaoling; Liu, Xuan; Shen, Wenchen; Liu, Ying; Zhou, Yan
Abstract : In utero electroporation (IUE) is commonly used to study cortical development of cerebrum by downregulating or overexpressing genes of interest in neural progenitor cells (NPCs) of small mammals. However, exogenous plasmids are lost or diluted over time. Furthermore, gene knockdown based on short‐hairpin RNAs may exert nonspecific effects that lead to aberrant neuronal migration. Genomic engineering by the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated 9 (Cas9) system has great research and therapeutic potentials. Here we integrate the CRISPR/Cas9 components into the piggyBac (PB) transposon system (the CRISPR/Cas9‐PB toolkit) for cortical IUEs. The mouse Sry‐related HMG box‐2 ( Sox2 ) gene was selected as the target for its application. Most transduced cortical NPCs were depleted of SOX2 protein as early as 3 days post‐IUE, whereas expressions of SOX1 and PAX6 remained intact. Furthermore, both the WT Cas9 and the D10A nickase mutant Cas9n showed comparable knockout efficiency. Transduced cortical cells were purified with fluorescence‐activated cell sorting, and effective gene editing at the Sox2 loci was confirmed. Thus, application of the CRISPR/Cas9‐PB toolkit in IUE is a promising strategy to study gene functions in cortical NPCs and their progeny. © 2016 Wiley Periodicals, Inc. Abstract : Embryonic mouse cortices were electroporated with the PB transposon vector PB‐SgSox2‐Cas9‐EGFP. Neural precursor cells stably expressing Cas9 protein, sgRNAs against Sox2, and EGFP (green) were abolished with SOX2 proteins (red).